2021
DOI: 10.1186/s42523-021-00076-6
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and resilience of great tit (Parus major) gut microbiomes to changing diets

Abstract: Background Gut microbial communities play important roles in nutrient management and can change in response to host diets. The extent of this flexibility and the concomitant resilience is largely unknown in wild animals. To untangle the dynamics of avian-gut microbiome symbiosis associated with diet changes, we exposed Parus major (Great tits) fed with a standard diet (seeds and mealworms) to either a mixed (seeds, mealworms and fruits), a seed, or a mealworm diet for 4 weeks, and examined the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 83 publications
5
34
0
Order By: Relevance
“…We found that Clostridium was significantly enriched in the foliage food group (Wilcoxon rank sum test, P , 0.05), followed by the fruit and omnivore food groups (Fig. 2C), which is consistent with the results observed in passerine birds that have plant-based diets (33). A similar CAZyme profile appeared in these 3 groups (foliage, fruit, and omnivore), whose diets contain high levels of plant cellulose (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…We found that Clostridium was significantly enriched in the foliage food group (Wilcoxon rank sum test, P , 0.05), followed by the fruit and omnivore food groups (Fig. 2C), which is consistent with the results observed in passerine birds that have plant-based diets (33). A similar CAZyme profile appeared in these 3 groups (foliage, fruit, and omnivore), whose diets contain high levels of plant cellulose (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…R. Soc. B 288: 20210446 as microbiomes (when bacterial phylogeny is not considered) are secondarily influenced by host diet, which is consistent with previously documented flexible responses in gut communities to diet changes [17,19,22,26]. Individual dietary intake of wild New Guinean birds varies greatly within a species [32], suggesting broader dietary niches than often assumed (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…These modifications could potentially affect the stability of avian gut microbial communities [10], because shorter gut retention leads to more fluctuating gut environments and potentially higher microbial turnover. Bird microbiomes are also highly variable between individuals of the same bird species [19][20][21] and tend to be malleable to dietary and environmental changes [19,[21][22][23][24][25][26]. Consequently, diet tends to affect gut microbiomes more than host phylogeny [17].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the order Clostridiales are abundant in the GM of many vertebrate taxa, including other insectivorous passerine species [97,98] and have previously been linked to an increase in immunological resistance to nest parasites in eastern bluebirds (Sialia sialis) [99]. A study on captive, juvenile ostriches (Struthio camelus), also showed that the abundance of ASVs in this order was reduced in the hindgut of diseased individuals that subsequently died, suggesting that they may be linked to host health and survival [10].…”
Section: Gm Variation and Survivalmentioning
confidence: 99%
“…A study on captive, juvenile ostriches (Struthio camelus), also showed that the abundance of ASVs in this order was reduced in the hindgut of diseased individuals that subsequently died, suggesting that they may be linked to host health and survival [10]. Species in the order Clostridiales play a role in carbohydrate and protein fermentation (for example during the digestion of insect prey) as well as the degradation of toxic by-products from this process [97,100]. The short-chain fatty acids produced from fermentation can be directly absorbed across the intestinal wall and used as an energy source by the host [94].…”
Section: Gm Variation and Survivalmentioning
confidence: 99%